The Next Generation of the FIBRE Software Architecture - Caled, Danielle; Salmito, Tiago; Santos, João F.; Ciuffo, Leandro; Rezende, José; Machado, Iara (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2017: Anais do VIII Workshop de Pesquisa Experimental da Internet do Futuro, 2017)
The FIBRE testbed is a large-scale research facility for experimentation on Future Internet technologies. To address specific requirements of the Brazilian federation, it was decided to commence a new development phase in which FIBRE would have its architecture completely revised. This paper presents an overview of the next generation of the software architecture envisioned for the FIBRE testbed.